200k views
15 votes
Y = 2(x – 3)2 - 4
Convert to standard form

User Dina
by
5.1k points

2 Answers

7 votes

Answer:

4x - y = 16

Explanation:

y = 2(x – 3)2 - 4

When written in standard form, this will be the answer --->

4x - y = 16

User Joakim M
by
4.6k points
10 votes

Answer:

y = 2x² - 12x + 14

Explanation:

The equation of a parabola in standard form is

y = ax² + bx + c ( a ≠ 0 )

Given

y = 2(x - 3)² - 4 ← expand (x - 3)² using FOIL

= 2(x² - 6x + 9) - 4 ← distribute parenthesis

= 2x² - 12x + 18 - 4

y = 2x² - 12x + 14 ← in standard form

User Tscpp
by
4.3k points